Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Pemerintah Kabupaten Karanganyar - Andre Kussuma Adiputra; Andri Apriyanti; Khaula Lutfiati Rohmah (Global Financial Accounting Journal, 2020)
This study aims to determine the financial performance of the Karanganyar Regency Government Budget Year 2015-2017 seen from: Analysis of Regional Income Variance, Analysis of Regional Income Growth, Decentralization Degree Ratio, Regional Finance Dependency Ratio, Regional Financial Independence Ratio, Analysis of Regional Expenditure Variance, Analysis of Regional Expenditure Growth, Regional Expenditure Suitability Ratio, Regional Expenditure Efficiency Ratio, and Value For Money Concepts. This research is a qualitative descriptive study. The technique of collecting data used in this study is documentation techniques. The data used is Secondary Data in the form of the Karanganyar Regency Government Budget Realization Report 2015-2017. The results showed that the financial performance of the Karanganyar Regency Government was generally said to be good. This can be seen from: (1) Analysis of Regional Income Variance which shows the number 100.86% (2) Analysis of Regional Income Growth which shows a positive growth of 7.82% (3) Decentralization Degree Ratio which shows 16.50% ( 4) Regional Finance Dependency Ratio which shows 83.17% (5) Regional Financial Independence Ratio which shows the number 19.84% (6) Analysis of Regional Expenditure Variance below 100% on average (7) Analysis of Regional Expenditure Growth with an average 3.76% (8) Regional Expenditure Suitability Ratio The Karanganyar District Government allocates a large portion of its expenditure budget for operating expenditure, which averages 76.92%, while for capital expenditure 16.01% (9) Regional Expenditure Efficiency Ratio which shows the number 89.08% (10) Value For Money concept which shows that the realization of regional income exceeds the amount of the regional income budget. However, the degree of decentralization is still low and the level of financial dependence on the central government and regional government is still high.